2016
DOI: 10.1038/srep39160
|View full text |Cite
|
Sign up to set email alerts
|

Water photolysis effect on the long-term stability of a fiber optic hydrogen sensor with Pt/WO3

Abstract: One of the technological challenges for hydrogen sensors is long-term stability and reliability. In this article, the UV-light irradiation was introduced into the hydrogen sensing process based on water photolysis effect of Pt/WO3. Ascribing to that, fiber optic hydrogen sensor with Pt/WO3 nanosheets as the sensing element was demonstrated with significantly improved performance of stability. Under UV irradiation, the hydrogen sensor exhibits higher sensitivity and resolution together with a smaller error rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In our previous manuscript, we have demonstrated that the response time of Pd/WO 3 based hydrogen sensor is no more than 33 min [28], so we have not repeated the experiments to measure the response time of the proposed sensor. What should be mentioned is that the response time may be improved by UV-light irradiation [29], doping graphene quantum dots [30], which will be carried out in our future work.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous manuscript, we have demonstrated that the response time of Pd/WO 3 based hydrogen sensor is no more than 33 min [28], so we have not repeated the experiments to measure the response time of the proposed sensor. What should be mentioned is that the response time may be improved by UV-light irradiation [29], doping graphene quantum dots [30], which will be carried out in our future work.…”
Section: Resultsmentioning
confidence: 99%
“…Chao et al doubled the LOD of ethanol/acetone [ 94 ], and significantly improved the response time and recovery time. The introduction of metal NPs effectively reduces the working temperature of oxide semiconductor materials, which can realize the gas sensor at room temperature [ 95 ]. The performance of fiber-LSPR based chemical sensors reported in recent years is compared in Table 2 .…”
Section: Fiber-lspr Chemical Sensorsmentioning
confidence: 99%
“…In 2016, the long-term stability of Pt-loaded WO 3 coating was studied by Zhong et al [52]. With the irradiation of ultraviolet light, the water photolysis effect of Pt-loaded WO 3 coating can be introduced into the hydrogen sensing process.…”
Section: Optical Fiber Grating Hydrogen Sensor Based On Exothermicmentioning
confidence: 99%
“…After heating the hydrogen sensitive film at higher temperature, the performance of hydrogen sensor can be recovered. More recently, the sensor stability can be significantly enhanced by ultraviolet irradiation [52], which provides a novel method to overcome the interference of humidity. As for optical fiber hydrogen sensors based on Pd and Pd alloys, the influence of humidity will be much more obvious.…”
Section: Challenges For Fiber Grating Hydrogen Sensormentioning
confidence: 99%